VARIABILIDADE E ESTRUTURA GENÉTICA POPULACIONAL DE Solanum mauritianum Scop. (SOLANACEAE) - Gobatto, Cláudia Regina (2017)
Solanum mauritianum, popularly known as “fumo-bravo”, is a pioneer and native angiosperm of the Atlantic Forest. This species has remarkable ecological importance in the recovery of disturbed areas. The knowledge of genetic variation within and among populations of S. mauritianum may be useful for the implementation of conservation strategies of this and other related species. The objective of this study was to evaluate the variability and population genetic structure of S. mauritianum using ISSR (Inter-Simple Sequence Repeat) molecular markers and to relate the data obtained with the biology of the species. For molecular analysis were used seven populations (218 plants) from the states of Paraná and Santa Catarina. The DNA of each plant was extracted and amplified by PCR (Polymerase Chain Reaction) using nine ISSR primers. Measures of growth and fruiting period of S. mauritianum were evaluated. The Nei's genetic diversity (h) and the Shannon diversity index (I) showed values of 0.32 and 0.49, respectively. The analysis of the distribution of groups of loci showed that the populations have high similarity. The AMOVA showed that most variation occurs within populations (84%) than among populations (16%). High values of gene flow were obtained (between 1.72 to 11.79) between populations and the PCoA showed no structuring. It was observed that Solanum mauritianum show an accelerated growth and continuous fruit production. This may explain the high values of genetic variability and gene flow and the low structuring of the species. The Mantel test showed no significant correlation between geographic and genetic distances for the populations studied. This situation may be related with the different environmental conditions where the populations of this study are located, and those subjected to the same climatic conditions are the most similar.